Protected Land Disturbance, Stress, and American Ecosystem Management - Spieles, Douglas J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Since John Muir and Gifford Pinchot championed the protection of land a century ago, ecologists and conservationists have struggled with simple questions of ecological management: exactly what aspects of our natural resources should we protect, and how should we protect them? At the heart of this debate lies the concept of the ecosystem$1 (Ba term that has ironically grown more difficult to define as our understanding of ecological relationships has evolved. In this compelling book, Doug traces the notion of the ecosystem from its early application in American land conservation through the modern approach to natural resources management. Doug makes the case that the classic ecosystem concept is as deeply ingrained in the American conservation movement as it is deeply flawed. As a result, many present-day land protection efforts are fixated on the preservation of an ideal set of species as a coherent and sustainable unit, even as ecological research increasingly suggests that no such unit exists. Through critical analysis of ecosystem management in theory and practice, Protected Land presents an argument for re-framing the human relationship with ecological systems to embrace, rather than suppress, the forces of change.s
Preface -- Four Ecosystems, Four Questions; Oak Openings, Ohio; Kissimmee River, Florida; Tallgrass Prairie, Kansas; Six Rivers National Forest, California; Four Questions -- Part 1: Ecosystems in Theory -- The Ecosystem Idea and Ideal; Preservation, Conservation, and Ecology; Gleason and Individualism; Leopoldian Preservation and Conservation; Hutchinson, Holism, and Individualism; The New Ecology; Preservation of the Ideal; Toward an Ecosystem Approach to Management -- A Thing is Right; The Adaptive Cycle; Diversity, Stability, Health and Integrity -- Disturbance, Stress, and Resilience; Disturbance; Resilience; Complications of Stress -- Invasion; Colonization and Succession; Factors of Colonization; Nonnative Invaders; Passengers and Drivers; Ecosystem Function and Service; Ecosystem Service and Invasion; Eradication; A Conservation Dilemma -- Part 2: Ecosystems in Practice -- Very Small Ecosystems; Microbial Ecosystems; Biofilms as Model Ecosystems; Biofilms as Patches; Micro- and Macro-Ecosystems -- Forested Ecosystems; The Forest Sanctuary; The Monongahela Experiment; Wilderness Management; Healthy Forests; Unmanaged Forest Succession -- Grassland Ecosystems -- Grasslands, Short and Tall; Prairie Restoration and Umbrella Species; Land Trust Grasslands -- Freshwater Ecosystems; Wetlands; Lakes; Rivers -- Saltwater Ecosystems; Intertidal Ecosystems; Subtidal Ecosystems; Deeper Water -- Protecting the Shifting Quilt; Holism, Strong and Weak; The Four Horsemen Revisited; Along the Continuum; Protecting the Shifting Quilt -- Index.
Keywords: Environmental sciences; Conservation biology; Environmental management; Environment; Environmental Management; Conservation Biology/Ecology.